Glacial Deposits in the Río del Peñón Formation (Late Carboniferous), Río Blanco Basin, Northwestern Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Río del Peñón Formation (Borrello, 1955 nom. subst. González y Bossi, 1986) forms the upper part of the late Paleozoic outcropping in the Río Blanco anticline (northwest Precordillera, La Rioja Province). This unit is predominantly composed of a thick (1270 m.) sandstone and mudstone sequence including thin levels of coal and scarce conglomerates (Scalabrini Ortiz, 1972; Scalabrini Ortiz and Arrondo, 1973; González and Bossi, 1986). These deposits represent a complex interfingering of shallow marine and fluvial deposits recording relative sea-level fluctuations during the Late Carboniferous-Early Permian. The Río del Peñón Formation overlies andesites and volcanic breccias of the Punta del Agua Formation (Fig. 1 and 2a).Despite well known Late Carboniferous glacigenic deposits from different localities within the Precordillera (López Gamundí, 1987, 1997; López Gamundí and Martinez, 2000; Marenssi et al., 2004; Limarino and Spalletti, 2006; Henry et al., in press), glaciogenic deposits have not been reported from the Río del Peñón Formation. This documentation of glacial-related sediments in this succession serves to further constrain our knowledge of the temporal and paleogeographic distribution of Gondwanan glacial deposits.